2015
DOI: 10.1039/c4nj01658k
|View full text |Cite
|
Sign up to set email alerts
|

Easily crosslinkable side-chain azobenzene polymers for fast and persistent fixation of surface relief gratings

Abstract: A series of side-chain azobenzene (azo) homo-and copolymers with easily crosslinkable Nhydroxysuccinimide carboxylate-substituted azo moieties and relatively low glass transition temperatures were synthesized for rapid and persistent fixation of surface relief gratings (SRGs). These azo polymers exhibited good thermal stability and their films proved easily crosslinkable within 4-15 min with 1,6-hexanediamine under mild conditions with the crosslinking rates of copolymer films being faster than 10 homopolymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 80 publications
(175 reference statements)
0
17
0
Order By: Relevance
“…Importantly, these films are very uniform, adherent to one another, and present a scalable way to make variable thickness STECs not limited by the spin‐coating approach. This engineering concept presents further opportunities to incorporate cross‐linking units onto the azobenzenes themselves in order to increase STF loading or to construct co‐polymers with cross‐linkable moieties, where the ratio of STF to cross‐links may be precisely controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, these films are very uniform, adherent to one another, and present a scalable way to make variable thickness STECs not limited by the spin‐coating approach. This engineering concept presents further opportunities to incorporate cross‐linking units onto the azobenzenes themselves in order to increase STF loading or to construct co‐polymers with cross‐linkable moieties, where the ratio of STF to cross‐links may be precisely controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Note that neither of the constituents contains any flexible chains that are conventionally used in designing small-molecule liquid-crystalline complexes, which in combination with the presence of the dimethylamino group should promote the surface patterning efficiency. 1043 , 1044 The high-temperature LC phase, in turn, should promote photoalignment. 1045 , 1046 The photoresponsive properties of the complex were indeed unique.…”
Section: Functional Systemsmentioning
confidence: 99%
“…The occurrence of the crosslinking in the blend films was confirmed by the difference of solubility between the crosslinked film and the uncrosslinked one (Figure S2, Supporting Information) . In addition, it has been demonstrated that the optical transparency of most of the azobenzene polymer films is hardly affected by the post‐crosslinking process, which is highly important for their practical applications . The PAZO/PU blend films mentioned below are crosslinked unless otherwise specified.…”
Section: Methodsmentioning
confidence: 86%
“…Thus in the PAZO/PU blend films, PU as the host material can provide favorable mechanical properties for the whole blend system. It should be mentioned that poly(methacrylate)‐type azobenzene polymers have rigid characteristics because of their backbones . Compared with the pure PU film, blend films (PAZO/PU = 9/91) show higher Young's modulus but smaller tensile strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation